Improving Students' Basic Emotional Management Skills Through the Emoji Card Method in the Malaysia International Teaching Volunteer Program (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
This review summarizes the literature discussing emotional management among children, particularly students in the Quranic Learning Center (Taman Pendidikan Al-Quran) in Kuala Lumpur, Malaysia, using the emoji card method. The ability to recognize, understand, and manage one's emotions and those of others greatly aids in building relationships and addressing life's challenges. Moreover, awareness of biases and self-emotions supports daily learning processes and enhances students' academic growth. The method employed for this community service was an experimental approach with a One-Group Pretest-Posttest design. The implementation stages included: (1) initial partner condition mapping, (2) introduction and administration of a pretest using a socio-emotional assessment sheet, (3) training using the "Storytelling & Role Play Card Emoji" method, (4) mentoring by volunteer teams and individual counseling sessions, and (5) posttest administration with identical measurements to the pretest. The findings demonstrated that emotional management training significantly improved students' skills in the Quranic Learning Center in Kampung Baru, Malaysia. These results are pivotal as they provide short-term solutions to common student issues and empower them to better adapt to their learning and social environments. Thus, these outcomes contribute to the development of more effective and sustainable community service programs, fostering better personality development in addressing challenges.